Mechatronics Capacity Building in Tanzania - Carlo Dante (GoAcademica Research & Publishing, 2019)
The paper deals with a capacity building project carried out by Politecnico di Milano and the three main technical universities of Tanzania aimed at stimulating high education in mechatronics and at giving professors the tools to design new mechatronics courses in the universities of the Country. This work is focused on the activities carried out at Mbeya University of Science and Technology (M.U.S.T.) where, within one week of intensive course, Tanzanian professors had the opportunity to develop a mechatronic system. The approach was aimed not just at teaching main subjects of a mechatronics course, but also at suggesting how these courses could involve university students on topics that will be a challenge for the emerging industry of the country.